Bioarchaeology of Pre-Columbian Mesoamerica : an interdisciplinary approach - Willermet, C. M. (Catherine M.), 1968-; Cucina, Andrea, 1966-; Larsen, Clark Spencer (University Press of Florida, 2018)
This edited volume presents work from both Mesoamerican-based and U.S.-based researchers who use a combination of cultural ethnohistorical, (bio)archaeological, dental, and chemical data in an interdisciplinary approach to research population history in pre-Columbian Mesoamerica. The goals for such a project are threefold: 1) to encourage more cross-fertilization of work between fields and subfields, in order to more appropriately address large regional questions of population history; 2) to explicitly address the theoretical and methodological challenges and rewards of interdisciplinary work; and 3) to introduce a larger audience to the state of interdisciplinary work in Mesoamerica.